2022
DOI: 10.1007/s00330-022-08536-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric bone MRI can improve CT-guided bone biopsy target selection in cancer patients and increase diagnostic yield and feasibility of next-generation tumour sequencing

Abstract: Objectives To evaluate whether multiparametric bone MRI (mpBMRI) utilising a combination of DWI signal, ADC and relative fat-fraction (rFF) can identify bone metastases, which provide high diagnostic biopsy yield and next-generation genomic sequencing (NGS) feasibility. Methods A total of 150 CT-guided bone biopsies performed by interventional radiologists (3/2013 to 2/2021) at our centre were reviewed. In 43 patients, contemporaneous DWI and rFF images, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Donners et al assessed the value of multiparametric MRI to identify viable bone metastases for biopsies. In their sample of 43 lesions, they observed lower, though not statistically significant, mean/median ADC in tumor-positive biopsies [41]. In contrast to the studies by Reischauer et al [40], Messiou et al [28] and Donners et al [41], which employed regions of interest (ROI), we used volume of interests (VOIs).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Donners et al assessed the value of multiparametric MRI to identify viable bone metastases for biopsies. In their sample of 43 lesions, they observed lower, though not statistically significant, mean/median ADC in tumor-positive biopsies [41]. In contrast to the studies by Reischauer et al [40], Messiou et al [28] and Donners et al [41], which employed regions of interest (ROI), we used volume of interests (VOIs).…”
Section: Discussionmentioning
confidence: 96%
“…In their sample of 43 lesions, they observed lower, though not statistically significant, mean/median ADC in tumor-positive biopsies [41]. In contrast to the studies by Reischauer et al [40], Messiou et al [28] and Donners et al [41], which employed regions of interest (ROI), we used volume of interests (VOIs). Going beyond previous studies, the validity of ADC measurements were ensured in our study by the use of a phantom containing the complete range of measured values found in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…We also advise taking a stepwise approach, where relatively fixed tumours are first investigated ( e.g. , MRI-guided bone biopsy [ 22 , 23 ], followed by more mobile tumours using internal motion correction techniques as has been applied in robotic lung biopsy without image fusion using breath hold monitoring [ 24 ]. For example, whereas rigid registration (as used in our study) might be more suitable for non-deformable structures with fixed internal points ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical translation should include the addition of a vacuum immobilisation mattress to reduce external motion [21]. We also advise taking a stepwise approach, where relatively fixed tumours are first investigated (e.g., MRI-guided bone biopsy [22,23], followed by more mobile tumours using internal motion correction techniques as has been applied in robotic lung biopsy without image fusion using breath hold monitoring [24]. For example, whereas rigid registration (as used in our study) might be more suitable for non-deformable structures with fixed internal points (e.g., bone), deformable structures may benefit from more complex deformable registration algorithms [25].…”
Section: Discussionmentioning
confidence: 99%
“…positron emission computed tomography PET has a high positive rate, but it doesn’t applicable to simple bone lesions, and the price is relatively high, which limited its application in clinic ( 11 , 12 ). Theoretically, the changes of biochemical indexes of bone metabolism during bone metastases are earlier than those in imaging ( 13 , 14 ). However, traditional biochemical indexes of bone metabolism with low specificity limits their application in the study of bone metastases ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%